Cleavage of the cII protein of phage lambda by purified HflA protease: control of the switch between lysis and lysogeny. - Cheng, H H (1988)
The activity of the cII protein of phage lambda is probably the critical controlling factor in the choice of the lytic or lysogenic pathway by an infecting virus. Previous work has established that cII activity is regulated through the turnover of cII protein; the products of the hflA and hflB loci of Escherichia coli are needed for a degradative reaction, and lambda cIII functions in stabilizing cII. By using the cloned hflA locus, we have purified a cII-cleaving enzyme that we term HflA. Purified HflA contains three polypeptides; at least two of the subunits are products of the hflA region, and the third is probably a cleavage product of the larger of these two hflA-encoded polypeptides. The HflA protease activity cleaves cII to small fragments. We conclude that the switch between lambda developmental pathways involves regulated cleavage of cII by the specific protease HflA.